PENGEMBANGAN E-LKPD BERBASIS LIVEWORKSHEET PADA MUTAN IPAS KELAS V SDN 4 BENTEK - Hena Anggreni; Muhammad Tahir; Muhammad Erfan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to develop instructional materials in the form of Interactive Electronic Worksheets (E-LKPD) based on Liveworksheet for the science subject (IPAS) for Grade V students at SDN 4 Bentek, and to determine the feasibility and student response to the developed instructional materials. The research method employed is the Research and Development (R&D) method with the ADDIE model consisting of the stages: analyze, design, development, implementation, and evaluation. Data collection techniques include interviews, observations, and questionnaires. Both qualitative and quantitative data are utilized. The results of the research and development indicate that the development of E-LKPD using Liveworksheets for science learning achieves a media expert score of 86.7% and a content expert score of 91.3%, which are categorized as very feasible. Meanwhile, the assessment given by students during the trial phase is 90%, also categorized as very feasible. This demonstrates that E-LKPD using Liveworksheet is suitable for use in science learning processes.